Cowpea response to planting date under different maize maturity types in West African Sudan savannah - Ewansiha, Sylvester U; Kamara, Alpha Y; Chiezey, Uchechuku F (Journal of Tropical Agriculture, 2014)
Intercropping is the traditional cropping system of the West African Sudan savannah with low system productivity. Timely growing together of adapted and compatible cowpea and maize cultivars is a potential way to improve the low productivity of the system. A two-year field experiment was conducted at Minjibir in Sudan savannah of Nigeria to determine the performance of medium and late maturing cowpea cultivars intercropped with extra-early and early maize cultivars at four and six weeks after maize. Early intercropping of cowpea with extra-early maize improved grain yield of cowpea (early maize, 405 kg ha-1 vs extra - early maize, 621 kg ha-1 ). Improved yield was also achieved with early intercropping of late maturing cowpea with maize (medium cowpea, 302 kg ha-1 vs late cowpea, 723 kg ha-1 ). Grain yield and crop value were maximized (884 kg ha-1 , $2411 ha-1 , respectively) with early intercropping of late maturing cowpea with extra-early maize. Therefore, late maturing cowpea can be recommended for intercropping with extra-early maize at four weeks after maize or less for maximum intercrop productivity.